Driving forces in modelling dynamic urban spatial growth for the George Town Conurbation (GTC) - Mahamud, Mohd Amirul; Samat, Narimah (2015)

(untitled)
Urban growth and transformation of spatial land use and land cover have affected various important physical environments, social, and economic activities. Researchers throughout the world have implemented diverse approaches in understanding the dynamic process of urban spatial growth where models have been developed to predict and simulate future urban growth and development. Model were developed based on the driving forces or factors that stimulate urban development. Therefore, the driving forces must be identified and analysed, especially for those that can be applied to forecast future changes and their potential environmental effects. The objective of this paper is to identify and analyse possible driving forces that promote urban spatial growth using the George Town Conurbation as a case study. The driving force were identity by reviewing recent research journals and articles regarding modelling urban growth. In addition, on-line survey was also generated and distributed to planners, academicians, researchers, and urban modellers to assess their perception on urban land use transformations and also measure the weight of potential drivers or factors that stimulate urban spatial growth. The findings indicated that distance to public amenities, cheap housing price, distance to workplace, and proximity to area that support new and growing businesses are among factors that are important determinants of urban development. The results provide valuable insights in modelling the dynamic urban spatial growth in future research.